2008
DOI: 10.1029/2008jd009999
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mixing ratio and isotopic composition of CO2 in urban air from the Los Angeles basin, California, between 1972 and 2003

Abstract: Atmospheric CO2 mixing ratios and C and O isotopic compositions are reported for the Los Angeles basin in southern California, a region renowned for its air pollution. Air samples collected midday on the Caltech campus in Pasadena, California, contained ∼30 ppm more CO2 in 1998–2003 than in 1972–1973 (averaging 397 ppm in 1998–2003 and 366 ppm in 1972–1973) compared to a 47 ppm change in background air CO2, yet the ranges of the carbon and oxygen isotopic compositions remained essentially constant. Because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 74 publications
(94 reference statements)
3
70
0
Order By: Relevance
“…On the diurnal time scale, δ 13 C S variability can be affected by the atmospheric mixing condition variation and the distribution of CO 2 sources (Wada et al, 2011;Sturm et al, 2006). In Wrocław, Poland and the Los Angeles basin, USA, the δ 13 C S differences over different time periods indicate changes in energy usage patterns (Gorka and Lewicka-Szczebak, 2013;Newman et al, 2008). In this study, the consistent δ 13 C S values of heating seasons I and II indicate that local energy consumption did not change during this period.…”
Section: Comparing the Characteristics Of δ 13 C S With Other Citiesmentioning
confidence: 47%
See 1 more Smart Citation
“…On the diurnal time scale, δ 13 C S variability can be affected by the atmospheric mixing condition variation and the distribution of CO 2 sources (Wada et al, 2011;Sturm et al, 2006). In Wrocław, Poland and the Los Angeles basin, USA, the δ 13 C S differences over different time periods indicate changes in energy usage patterns (Gorka and Lewicka-Szczebak, 2013;Newman et al, 2008). In this study, the consistent δ 13 C S values of heating seasons I and II indicate that local energy consumption did not change during this period.…”
Section: Comparing the Characteristics Of δ 13 C S With Other Citiesmentioning
confidence: 47%
“…Measurements of δ 13 C only have been performed at 4 sites: Dallas, Texas, USA (Clark- Thorne and Yapp, 2003); Paris, France (Lopez et al, 2013;Widory and Javoy, 2003); Bangalore City, Karnataka State, India (Guha and Ghosh, 2010); and Wrocław, Poland (Gorka and Lewicka-Szczebak, 2013). Both δ 13 C and δ 18 O observations have been conducted at another 4 sites: Kraków, Poland (Zimnoch et al, 2012, Zimnoch et al, 2004; Bern, Switzerland (Sturm et al, 2006); and Los Angeles Basin, California, USA (Djuricin et al, 2010;Newman et al, 2008). Only 3 urban sites have had long-term continuous observations of the mixing ratio and isotopic composition by IRIS technology.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Observations have been made discontinuously at Caltech since the early 1970s [Newman et al, 2008]. Analysis of carbon isotopes from whole air flask samples has been performed to assess the observed CO 2 attributable to local emissions, and it was found that~10 ppm more CO 2 was attributable to local emissions in the 1970s than the early 2000s, in seeming contrast to the known emissions increase in that time frame [Newman et al, 2008].…”
Section: Caltechmentioning
confidence: 99%
“…Analysis of carbon isotopes from whole air flask samples has been performed to assess the observed CO 2 attributable to local emissions, and it was found that~10 ppm more CO 2 was attributable to local emissions in the 1970s than the early 2000s, in seeming contrast to the known emissions increase in that time frame [Newman et al, 2008]. This finding can possibly be explained by analysis of the footprint of the Caltech site, seen in Figure 2a.…”
Section: Caltechmentioning
confidence: 99%
“…Numerous types of sites have been used to measure atmospheric CO 2 , such as: surface observatories (Idso et al, 2001;Newman et al, 2008;Ramonet et al, 2010;Rice and Bostrom, 2011;Pérez et al, 2012), balloon soundings (Bischof et al, 1980;Li et al, 2014), aircraft measurements (Bischof et al, 1980;Lloyd et al, 2002;Machida et al, 2002;Sidorov et al, 2002;Gurk et al, 2008;Shashkov et al, 2011;Sun and De Wekker, 2011;Sweeney et al, 2015), tall towers (Bakwin et al, 1995;Haszpra et al, 2005;Haszpra et al, 2012), and mountain-top observatories (Goldman, 1974;Thoning et al, 1989;Sturm et al, 2005;De Wekker et al, 2009;Ramonet et al, 2010;Brooks et al, 2012). Even though there are numerous methodologies for the measurement of CO 2 and data on atmospheric CO 2 concentrations have been available since the late 1950s, atmospheric chemistry models still have difficulty estimating CO 2 concentrations in conditions other than in a well-mixed planetary boundary layer (Haszpra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%